Metabolomics analysis of mechanism of improving quality of Schisandrae chinensis fructus by NO combining with high-temperature stress - Zhaoping Meng; Wei Zhang; Zixian Guo; Liyang Wang; Wenfei Liu; Ling Cao; Yuhua Zhang; Xiangcai Meng (PLoS ONE, 2025)
The fruits of Schisandra chinensis (Turcz.) Baill. (Schisandrae chinensis fructus) are a well-known herbal medicine, known for its hepatoprotective, antidepressant, antioxidant, and sedative-hypnotic properties. Over-exploitation of wild resources led to the rise of cultivation, along with a decrease in quality. Exposure of plants to adversity must generate substantial quantities of reactive oxygen species (ROS) and result in cellular damage. In response, secondary metabolites are produced to neutralize ROS; these secondary metabolites are usually the active ingredient of herbal medicine, so the quality of herbal medicine is closely related to the environment and ROS. The interplay of exogenous Nitric Oxide (NO, supplied as sodium nitroprusside) and high-temperature stress can simulate adversity and improve the quality of Schisandrae chinensis fructus; neverless, the underlying mechanism remains largely unexplored. In this study, we examined the changes in intracellular ROS levels as well as phenylalanine deaminase activities after stress and analyzed the metabolic changes using ultra performance liquid chromatography-quadrupole time-of-flight tandem mass spectrometry (UPLC-Q-TOF-MSE). The results showed that the level of superoxide anion (O2.−) and H2O2 increased by 25.8% and 331%, respectively, the activity of phenylalanine aminotransferase (PAL) by 69.3% on the 2nd day, indicating that combination of exogenous NO with high-temperature stress could lead to physiological states of adversity stress. Twenty-two differential metabolites (VIP ≥ 1) were identified using untargeted metabolomics. 3 primary metabolites, namely mannose, pyruvate, and shikimic acid, together with 2 secondary metabolites, phenylalanine and mevalonic acid, were observed to decrease. 17 secondary metabolites, including Schisandrin A, Schisandrin B, Schisandrin C, Gomisin D, Gomisin G, Gomisin H, Benzoylgomisin H, Benzoylgomisin O,Angeloylgomisin P, Catechin, Isorhamnetin, Luteolin, Cinnamic acid, Hydroxycinnamic acid, Hexahydrocurcumin, Coniferyl alcohol, Phenylalanine, Terpinolene and Mevalonic acid, exhibited increases in their levels by 10.64, 1.84, 1.40, 1.64, 4.46, 8.18, 1.72, 10.20, 2.08, 1.27, 1.57, 1.18, 2.01, 1.12, 1.88, 1.15, and 3.17-fold, respectively. Under stress conditions, intracellular ROS levels increased, and a significant portion of primary metabolites were used for the biosynthesis of secondary metabolites with higher antioxidant activity. This redistribution of metabolic flows from basal metabolism to secondary metabolism to defend against ROS. The combination of exogenous NO with high-temperature enhances secondary metabolism of Schisandra chinensis fruit, which opens new avenues for production of high-quality Schisandra chinensis fructus.